Regulation of Spindle Pole Function by an Intermediary Metabolite - Nickas, Mark E. (The American Society for Cell Biology, 2004)
Spore formation in the yeast Saccharomyces cerevisiae depends on a modification of spindle pole bodies (SPBs) at the onset of meiosis II that allows them to promote de novo membrane formation. Depletion of the environmental carbon source during sporulation results in modification of only one SPB from each meiosis II spindle and formation of a two-spored ascus, called a nonsister dyad (NSD). We have found that mutants impaired in the glyoxylate pathway, which is required for the conversion of acetate to glucose, make NSDs when acetate is the primary carbon source. Wild-type cells make NSDs when the carbon source is glycerol, which is converted to glucose independently of the glyoxylate pathway. During NSD formation in glycerol, only the two SPBs created at the meiosis I/II transition (“daughters”) are modified. In these conditions, the SPB components Mpc70p and Spo74p are not recruited to mother SPBs. Moreover, cooverexpression of Mpc70p and Spo74p suppresses NSD formation in glycerol. Our findings indicate that flux through the glyoxylate pathway during sporulation regulates modification of mother SPBs via recruitment of Mpc70p and Spo74p. These results define a cellular response in which the accumulation of an intermediary metabolite serves as a measure of biosynthetic capacity to regulate the number of daughter cells formed.